A Novel Approach to Assess Occupational Risks at Welding Processes in Shipbuilding Industry - Karamustafa, Merve; Cebi, Selcuk (OLD CITY PUBLISHING INC, 2023)
The welding process is one of the most common manufacturing techniques used in the shipbuilding industry. The risk assessment of welding processes is important in terms of occupational health and safety because of being a laborintensive operation. In the literature, fuzzy sets-based methods are newly proposed to the literature to consider uncertainties in the traditional risk assessment methods. However, none of them considers the inconsistency in the assessment although the probability of occurrence and severity of consequence may vary depending on the specialist assessment. For this, we propose a new risk assessment method to consider both uncertainty and inconsistency in the risk assessment process by using truth, indeterminacy and falsity parameters to assess the probability of risk occurrence and sever-ity of risk consequence. Then, a fuzzy inference-based if-then rules structure is used to obtain the risk magnitude. Thus, the situation before and after the precautions are taken are analyzed together.
Keywords: Risk Management; fuzzy inference system; neutrosophic set theory; occupational health and safety; MODEL; ACCIDENTS; HEALTH; Computer Science; Science & Technology - Other Topics